Study on the removal of pesticide in agricultural run off by granular activated carbon Bioresource Technology - Azizah, Endut; Ahmad, Jusoh; Hartini, W,J,H; Noraini, Ali (2011)
In this botch study the adsorption c/ malothon by usong granular actnorled carbon Nth different promoters due to the panocla sae dosage of carbons as Wet as the innsal c oncenualron of rnalathiOn was noaogal.d Batch teals was cached out to delarthne the pctentral and the efectneness of panda acirated carbon 'GAG) in mom) of pestrcule III agscultural fun dl The pander subverted caton coconut shell and palm shells were used and analyzed as the adsorbent material The Langmuir and Freundlich adsorption isotherms models awe applied to describe the characteristics of adsorption I:eh/trio, EquAbnocn data Sued net etth the Langmun model and Freurulloch model web mammon adsorption capacey d 909 I mogrg The lesuU indicate that the GAC could be used to *dear/els, adsorb poshede (rnalathean) from agncritural tuna (C) 2010 Elsevier Ltd All nsehs resorted